Modeling of counter-current multistage extraction of Moringa oleifera leaves using a mechanistic model - Vázquez-León, Lucio Abel; Olguín-Rojas, J. A.; Páramo Calderón, Delia Esther; Palma, Miguel; Barbero, Gerardo F.; Robles-Olvera, V. J.; García-Alvarado, M. A.; Rodríguez-Jimenes, G. C. (Food and Bioproducts Processing, 2019)
Antioxidant extracts obtained from natural products is highly relevant for the food, chemical and pharmaceutical industries. Moringa oleifera leaves contain significant levels of phenolic compounds with antiradical activity. Counter-current multistage extraction (CME) has been developed for the extraction of M. oleifera leaves. A mixture of ethanol:water 80:20 (w/w) was used as extraction solvent. The effects of extraction stage numbers, temperature, extraction time and solvent to sample ratio on the extraction yield were investigated. Process conditions of CME were optimized using a mechanistic model conceptualized by our work group. Under optimum process conditions (three stages, 120 min extracting time for every stage, 55 °C temperature and 0.03 g/g solvent to sample ratio) CME process offers high extraction yield and considerable savings in time, energy and solvent consumption.
Keywords: Moringa oleifera; Extracción multietapa a contracorriente; Compuestos fenólicos